2007
DOI: 10.1016/j.carres.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Recent studies on reaction pathways and applications of sugar orthoesters in synthesis of oligosaccharides

Abstract: Abstract-Formation of sugar-sugar orthoesters consisting of a fully acylated mono-or disaccharide donor and a partially protected mono-or disaccharide acceptor is regioselective, and rearrangement of the orthoesters via RO-(orthoester)C bond cleavage gives a dioxolenium ion intermediate leading to 1,2-trans glycosidic linkage. The activity order of hydroxyl groups in the partially protected mannose and glucose acceptors is 6-OH > 3-OH > 2-or 4-OH. The coupling reactions with acylated glycosyl trichloroacetimid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(39 citation statements)
references
References 71 publications
1
37
0
1
Order By: Relevance
“…The orthoester intermediates thus obtained can be transformed in situ into the desired glycosides by the addition of more of the catalyst, by extending the reaction time, or by other means. [103] This rearrangement usually leads to 1,2-trans glycosides through different possible pathways [104] and was used to develop new strategies for the regio-and stereoselective synthesis of oligosaccharides. [105] Nevertheless, additional studies, most notably by Wu and Kong, revealed that the rearrangement can also give 1,2-cis-linked products [106] in a transformation that does not conform with the classical concept of neighboring-group participation.…”
Section: 2-orthoesters Of Aldosesmentioning
confidence: 99%
“…The orthoester intermediates thus obtained can be transformed in situ into the desired glycosides by the addition of more of the catalyst, by extending the reaction time, or by other means. [103] This rearrangement usually leads to 1,2-trans glycosides through different possible pathways [104] and was used to develop new strategies for the regio-and stereoselective synthesis of oligosaccharides. [105] Nevertheless, additional studies, most notably by Wu and Kong, revealed that the rearrangement can also give 1,2-cis-linked products [106] in a transformation that does not conform with the classical concept of neighboring-group participation.…”
Section: 2-orthoesters Of Aldosesmentioning
confidence: 99%
“…[8] Orthoesters can be rearranged under acidic conditions to afford the corresponding glycoside. [9] However, the resilience of the orthoester and the acid sensitivity of the unsaturated alcohol combined to impair our efforts in this direction. For example, the use of a wide range of acids returned starting orthoester (e.g.…”
mentioning
confidence: 99%
“…Activation of a mixture of alcohol 14 and trichloroacetimidate 16 at 0 °C with 0.1 equiv of BF 3 ·Et 2 O provided disaccharide 26 in only 21% yield, with a 1,2-glycosyl orthoester as the major product (40%). Orthoesters are common by-products of glycosylation reactions and typically rearrange under acidic conditions to give trans -linked glycosides [43]. Thus, 14 and 16 were treated with 0.25 equiv of an alternative Lewis acid, TMSOTf, and allowed to react for a longer time to allow the intermediate orthoester to isomerize.…”
Section: Resultsmentioning
confidence: 99%